Benchmarking Water Oxidation Catalysts Based on Iridium Complexes: Clues and Doubts on the Nature of Active Species. Issue 22 (2nd November 2017) - Menendez Rodriguez, Gabriel; Gatto, Giordano; Zuccaccia, Cristiano; Macchioni, Alceo
Abstract: Water oxidation (WO) is a central reaction in the photo‐ and electro‐synthesis of fuels. Iridium complexes have been successfully exploited as water oxidation catalysts (WOCs) with remarkable performances. Herein, we report a systematic study aimed at benchmarking well‐known Ir WOCs, when NaIO4 is used to drive the reaction. In particular, the following complexes were studied: cis ‐[Ir(ppy)2 (H2 O)2 ]OTf (ppy=2‐phenylpyridine) (1 ), [Cp*Ir(H2 O)3 ]NO3 (Cp*=1, 2, 3, 4, 5‐pentamethyl‐cyclopentadienyl anion) (2 ), [Cp*Ir(bzpy)Cl] (bzpy=2‐benzoylpyridine) (3 ), [Cp*IrCl2 (Me2 ‐NHC)] (NHC=N‐heterocyclic carbene) (4 ), [Cp*Ir(pyalk)Cl] (pyalk=2‐pyridine‐isopropanoate) (5 ), [Cp*Ir(pic)NO3 ] (pic=2‐pyridine‐carboxylate) (6 ), [Cp*Ir{(P(O)(OH)2 }3 ]Na (7 ), and mer ‐[IrCl3 (pic)(HOMe)]K (8 ). Their reactivity was compared with that of IrCl3 ⋅ n  H2 O (9 ) and [Ir(OH)6 ] 2− (10 ). Most measurements were performed in phosphate buffer (0.2 m ), in which2, 4, 5, 6, 7, and10 showed very high activity (yield close to 100 %, turnover frequency up to 554 min −1 with10, the highest ever observed for a WO‐driven by NaIO4 ). The found order of activity is:10 >2 ≈4 >6 >5 >7 >1 >9 >3 >8 . Clues concerning the molecular nature of the active species were obtained, whereas its exact nature remains doubtfully. Abstract : True nature : The activity of archetypal iridium water oxidation catalysts is evaluated under exactly the same experimental conditions, exploiting NaIO4 as electron acceptor. [Ir(OH)6 ] 2− is found to be the most active catalysts reaching a record value for NaIO4 ‐driven water oxidation. Comparative kinetic analysis suggests that the active species has to be molecular in nature.